A comparison between laparoscopy and hysteroscopy approach in treatment of cesarean scar pregnancy. Issue 43 (23rd October 2020) - Zhang, Xiaolei; Pang, Yingxin; Ma, Yanhui; Liu, Xin; Cheng, Lin; Ban, Yanli; Cui, Baoxia
Abstract : Abstract: The aim of the study was to compare the efficacy of laparoscopy and hysteroscopy for the treatment of cesarean scar pregnancy (CSP) and analyze the clinical factors associated with successful selection for hysteroscopic or laparoscopic treatment of CSP. We retrospectively studied 112 cases of CSP that were treated by laparoscopy and/or hysteroscopy in our hospital from December 2014 to December 2017. In total, 72 of these patients underwent ultrasound-guided curettage and hysteroscopic resection without uterine scar defect repair. Fourty of these patients underwent laparoscopic resection and repair of the uterine scar defect. We analyzed the different clinical variables between the 2 groups and identified the clinical factors which could predict the need for the laparoscopic repair of uterine scar defect. Results showed that laparoscopy and hysteroscopy were safe ways to treat CSP, and no patient underwent hysterectomy. The β-hCG level in both of the 2 groups decreased to normal 4 to 8 weeks after surgery. There were significant differences between the hysteroscopy group and laparoscopy uterine scar repair group in terms of days of amenorrhea, gestational sac diameter, myometrial thickness, operation time, intraoperative blood loss, and hospitalization duration ( P < .05). Logistic regression analysis showed that the days of amenorrhea, gestational sac diameter and myometrial thickness were independent risk factors for CSP treated by minimally invasive surgery, which were also shown by ROC curve analysis to be predictors of the need for the repair of the uterine scar defect, with optimal cutoffs of 52.50 days, 3.25 cm, and 2.05 mm, respectively; and the areas under their corresponding ROC were 0.721, 0.851, and 0.927, respectively. We conclude that laparoscopy and hysteroscopy are safe and efficient minimally invasive procedures for the treatment of CSP. The days of amenorrhea, gestational sac diameter and myometrial thickness may be key factors associated with successful selection for hysteroscopic or laparoscopic treatment of CSP.